Relationship of Serum Adiponectin Levels with Lipid Profile in Diabetic and Non-Diabetic Pregnant Women - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Adiponectin levels correlate positively with high-density lipoprotein (HDL), and negatively with serum triglyceride (TAG), low-density lipoprotein (LDL), and serum total cholesterol (TC).Aims:To find the relationship of serum adiponectin levels with lipid profiles in diabetic and non-diabetic pregnant women.Settings and Design:The study was performed in four public hospitals and one private tertiary care hospital in Peshawar, Pakistan. This study was a cross-sectional study.Methods and Material:Group A included 100 non-diabetic pregnant women, and Group B included 100 women with gestational diabetes mellitus. Inclusion criteria were a single fetus, 24 to 40 weeks pregnancy, with or without gestational diabetes. Exclusion criteria were multiple pregnancies, pre-existing diabetes, and other comorbidities. The serum adiponectin level and lipid profile of both groups were measured.Statistical Analysis Used:Descriptive analysis of all the variables was done. Independent-sample T-tests, Pearson’s correlations, and binary logistic regression analyses were performed on SPSS version 20.Results:Adiponectin level was significantly lower in Group B (2.17 ± 1.84 μg/mL) as compared to Group A (9.94 ± 4.81 μg/mL). HDL level was significantly lower than normal in Group B. TC and LDL levels were higher than normal in both groups. A statistically significant relationship was found between adiponectin and HDL only. Binary logistic regression analysis showed that low adiponectin levels could predict diabetes in pregnancy.Conclusions:Regression analysis could not establish any relationship between adiponectin and lipid profile. However, adiponectin levels could show a relationship with the diabetic group. Hence adiponectin levels could possibly prove to be a biomarker of GDM.